A research study on air traffic controller (ATCO) crossing event analysis for wide angle crossing - Lim, Yun Yi (2019)
As air traffic demand continue to grow in the upcoming years, Air Traffic Management (ATM) are being challenged to provide safe and orderly flight in the sky. Many automation tools had been implemented to aid Air Traffic Controllers (ATCOs) and increase the airspace capacity. The role of the ATCOs would then shift towards more of active monitoring than controlling. Thus it is important to examine how well controllers perform monitoring for crossing and conflict resolution, when they are removed from tactical control. Past research studies have discovered that there is indeed difference in the visual monitoring behaviour between controllers with different expertise level via the use of eye tracking technology. However, these past researchers have limited effort in trying to map the movement of the eye ball to the radar in real-time. This project aims to establish a peak alignment model to study the crossing monitoring behaviour of participants and distinguish the difference between the expertise levels. It was found that there is a clear difference between ATCOs with different level of expertise under different airspace factors. Thus, the model can be used as an assessment method for ATCOs in the future.